Seoul : The Monocle Travel Guide Series (Berlin : Gestalten, 2018)
The South Korean capital is energetic and sprawling; it's a 24-hour city that's home to some 10 million people and plenty of brightly lit billboards, skyscrapers and shops. But that's not all. Beyond the colourful clutter are innoviative building projects, lush green spaces, world-class museums and a tasty spread of places to eat and drink. The Monocle Travel Guide to Seoul looks past the dazzling lights to discover what, and who, have brought this late-blooming city careering into the 21st century. Its streets may be tricky to navigate but Seoul's inhabitants are turning it into an accessible and playful metropolis that respects its roots while embracing the future. We've amassed our favourite architectural feats - from a women's university to an ivy-clad red-brick church - and sipped our way through the snappiest coffee shops, including one in an old printing press. The hotels we long to hunker down in vary from glittering glass towers to traditional hanok. Plus, we've mapped out four top-notch itineraries. Whatever you want and whenever you wnat it, Seoul has you covered, be it late-night trips to the sauna or early-morning treks around the hills. Hike up your hanbok and come and meet the people putting their hearts into Seoul.
Keywords: Reisgids; Seoul